(untitled) (Community Based Medical Journal, 2022)
Congenital anomalies of kidney and urinary tract (CAKUT) is a group of abnormalities affecting the kidneys or other structures of the urinary tract that include ureters, urinary bladder and urethra. CAKUT include renal agenesis or hypodysplasia, multicystic dysplastic kidney, ureteropelvic junction obstruction, duplication of the pelvis, ureter, and/or kidney, congenital megaureter, ureterovesical junction obstruction, vesicoureteral reflux and posterior urethral valves. Those results from abnormal development of the urinary system and is present from birth (congenital), although the abnormality may not become apparent until later in life. The clinical spectrum of CAKUT has significant impact on long-term patient survival. We observed that the causes of CAKUT are complex, usually combination of genetic and environmental factors contribute to the developmental abnormalities of kidney and urinary tract in foetus. The genetic factors involved in most cases of CAKUT are unknown; however, syndromic CAKUT is caused by changes in the genes associated with the particular syndrome. Variations in the same genes can also underlie some cases of isolated CAKUT. This review paper aims to discuss genetic basis of CAKUT, i.e., identifying different genes involved in syndromic and non-syndromic CAKUT. Modern genetic testing facilities can provide a precise diagnosis that can help individualize clinical care by screening for specific complications, facilitate medical decision making, and provide better genetic counseling. CBMJ 2022 January: vol. 11 no. 01 P: 69-74